2015
DOI: 10.1371/journal.pone.0117222
|View full text |Cite
|
Sign up to set email alerts
|

Puffing Topography and Nicotine Intake of Electronic Cigarette Users

Abstract: BackgroundPrior electronic cigarette (EC) topography data are based on two video analyses with limited parameters. Alternate methods for measuring topography are needed to understand EC use and nicotine intake.ObjectivesThis study evaluated EC topography with a CReSS Pocket device and quantified nicotine intake.MethodsValidation tests on pressure drop, flow rate, and volume confirmed reliable performance of the CReSS Pocket device. Twenty participants used Blu Cigs and V2 Cigs for 10 minute intervals with a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
162
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(200 citation statements)
references
References 40 publications
12
162
2
1
Order By: Relevance
“…Nevertheless, recent findings suggest that puff velocity does not influence nicotine yield (Talih et al, 2014), >10 s puffs are rare (only 1.17% of all puffs in our study), and the CReSS device shares similar recording issues with a limit of 43 puffs. Despite methodological differences, puff durations under high and low nicotine conditions observed here are similar to those previously reported in experienced users using newer generation devices (Farsalinos et al, 2014;Hua et al, 2013) but longer than those reported for cartomiser (first-generation) devices (Behar, Hua, & Talbot, 2015) and tobacco cigarettes (Hua et al, 2013). Our study was conducted in a controlled laboratory environment which may not reflect real-world puffing behaviour (Robinson, Hensel, Morabito & Roundtree 2015) possibly over-estimating puffing.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, recent findings suggest that puff velocity does not influence nicotine yield (Talih et al, 2014), >10 s puffs are rare (only 1.17% of all puffs in our study), and the CReSS device shares similar recording issues with a limit of 43 puffs. Despite methodological differences, puff durations under high and low nicotine conditions observed here are similar to those previously reported in experienced users using newer generation devices (Farsalinos et al, 2014;Hua et al, 2013) but longer than those reported for cartomiser (first-generation) devices (Behar, Hua, & Talbot, 2015) and tobacco cigarettes (Hua et al, 2013). Our study was conducted in a controlled laboratory environment which may not reflect real-world puffing behaviour (Robinson, Hensel, Morabito & Roundtree 2015) possibly over-estimating puffing.…”
Section: Discussionsupporting
confidence: 79%
“…A 15‐minute break between the 2 exposure sessions was given so that the animals could access fresh air, food, and water. The puff duration was 3 seconds, puff interval 1 minute, and the puff volume was 50 mL, all of which mimics real‐life exposure scenarios 24, 25, 26, 27, 28, 29, 30, 31, 32, 33. As for the controls or control mice, they were matched in terms of age and sex (ie, 10‐week‐old males), and were exposed to clean air.…”
Section: Methodsmentioning
confidence: 99%
“…It may be that the users puff harder/more frequently on E-Cig devices that are less efficient at delivering nicotine to maintain sufficient plasma nicotine levels. Indeed, data suggested that users were able to maintain constant nicotine uptake, despite switching brands (15). Importantly, until a greater consensus is reached, these data suggest that a modified Canadian Intense profile may be a suitable parameter for studying E-Cig aerosol generation.…”
Section: Tissue/cell Type Effectsmentioning
confidence: 95%
“…To date, no consensus exists on how to set E-Cig parameters, and nothing comparable to the Canadian Intense profile has been developed. However, Farsalinos et 15). These authors studied several different types of E-Cig and found that parameters varied only slightly with the type of E-Cig used.…”
Section: Tissue/cell Type Effectsmentioning
confidence: 99%